Map of North America: from the latest authorities showing the proposed railroad routes from the Atlantic to the Pacific Oceans. - J.H. Colton & Co. (J.H. Colton & Co., 1849)
Map shows mid-nineteenth century major cities, existing and proposed railroad routes, Mexico, British America, Russian Possessions [Alaska], Central America, the West Indies, areas of Indian habitation by tribe with populations numbers, western U.S. territories. Includes table of distances, geographical statistics, notes, and 1 illustration. Relief shown by hachures and spot heights. Scale [ca. 1:15,000,000].